Akibat Hukum Kantor Pajak Sebagai Kreditor Pemohon Pernyataan Pailit - Andani, Devi (UIR Press, 2023)
This study aims to determine the legal consequences of the tax office as a creditor of the applicant for bankruptcy. This research is qualitative research and normative legal research. Research data was collected using literature and document studies. The data that has been collected will be identified and arranged systematically, including data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. Then all the data obtained from the literature study and document study were relevant to related theories and written descriptively and analyzed qualitatively. The results of this study show that the Tax Office as creditor of the applicant for bankruptcy has the legal consequence that the process of bankruptcy application submitted by the Tax Office as debtor is possible. So for creditors who have debts in the form of taxes, the Tax Office as debtor can submit a request for bankruptcy proceedings. The Tax Office has a very high-ranking statutory priority/privilege. States have general statutory priority rights for unpaid taxes, interest, fines, and fees. This special position ends 2 (two) years after the tax assessment date. Even though the Tax Office is a government institution that has its authority to carry out efforts to collect and pay off taxes, based on the provisions for filing a bankruptcy declaration application or to act as another creditor in a bankruptcy declaration application, this should be implemented consistently. Thus, tax debts have the possibility of being asked for repayment by taxpayers through the mechanism of requesting a bankruptcy declaration.